2016
DOI: 10.1099/mic.0.000324
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trehalose content, enzyme activity and gene expression related to trehalose metabolism in Flammulina velutipes under heat shock

Abstract: Trehalose plays important roles in the protection of organisms against adverse environmental conditions. The growth and development of Flammulina velutipes is regulated and controlled under complex external conditions. This study investigated the effect of heat stress on trehalose metabolism in mycelia and fruiting bodies. The activities of enzymes involved in trehalose metabolism, the transcriptional levels of the corresponding genes and the trehalose content in the mycelia of Flammulina velutipes strain Dan3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
(22 reference statements)
1
24
0
Order By: Relevance
“…Similar to PoTPS1, Trep demonstrated high activity in trehalose synthesis after 15 h of heat treatment (Fig. 7A), consistent with the results obtained in Flammulina velutipes, wherein the activity of TPS1 and Trep in trehalose synthesis direction reached the highest level after 8 and 6 h of heat treatment, respectively [12]. Moreover, the co-effects of Trep in trehalose degradation direction and NTH resulted in low trehalose degradation activity ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to PoTPS1, Trep demonstrated high activity in trehalose synthesis after 15 h of heat treatment (Fig. 7A), consistent with the results obtained in Flammulina velutipes, wherein the activity of TPS1 and Trep in trehalose synthesis direction reached the highest level after 8 and 6 h of heat treatment, respectively [12]. Moreover, the co-effects of Trep in trehalose degradation direction and NTH resulted in low trehalose degradation activity ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that Trep responded more intensely to heat treatment than Po TPS1 (Figs. B, C and B, D), whereas in F. velutipes , Trep is not more sensitive than TPS1 under heat treatment , suggesting different expression patterns in different organisms.…”
Section: Discussionmentioning
confidence: 90%
“…Although, the heat shock response has been studied in considerable detail in yeast and plant (McAlister and Finkelstein 1980;Richter et al 2010;Song et al 2012), the mechanism of heat shock response in basidiomycetes remains elusive. Mushrooms evolved various strategies to response and alleviate heat shock stress, including HSPs synthesis, trehalose accumulation, and reactive oxygen species scavenging (Chen et al 2017;Liu et al 2016Liu et al , 2018Liu et al , 2019Wang et al 2017). In this study, we focused on a HSPs gene involved in heat shock response in H. marmoreus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liu et al (2016) reported that the trehalose contents and trehalase activities change during fruit-body formation in Flammulina veltipes (Liu et al 2016). Earlier, the acid trehalase, from a culture filtrate of Lentinus edodes, was purified and characterized by Murata et al (2001) (Murata et al 2001); this enzyme was composed of two identical subunits (71-91 kDa) and contained carbohydrate molecules.…”
mentioning
confidence: 99%